An update on the Society for Immunotherapy of Cancer consensus statement on tumor immunotherapy for the treatment of cutaneous melanoma: version 2.0. Issue 1 (30th May 2018) - Sullivan, Ryan J.; Atkins, Michael B.; Kirkwood, John M.; Agarwala, Sanjiv S.; Clark, Joseph I.; Ernstoff, Marc S.; Fecher, Leslie; Gajewski, Thomas F.; Gastman, Brian; Lawson, David H.; Lutzky, Jose; McDermott, David F.; et al.
Abstract : Background: Cancer immunotherapy has been firmly established as a standard of care for patients with advanced and metastatic melanoma. Therapeutic outcomes in clinical trials have resulted in the approval of 11 new drugs and/or combination regimens for patients with melanoma. However, prospective data to support evidence-based clinical decisions with respect to the optimal schedule and sequencing of immunotherapy and targeted agents, how best to manage emerging toxicities and when to stop treatment are not yet available. Methods: To address this knowledge gap, the Society for Immunotherapy of Cancer (SITC) Melanoma Task Force developed a process for consensus recommendations for physicians treating patients with melanoma integrating evidence-based data, where available, with best expert consensus opinion. The initial consensus statement was published in 2013, and version 2.0 of this report is an update based on a recent meeting of the Task Force and extensive subsequent discussions on new agents, contemporary peer-reviewed literature and emerging clinical data. The Academy of Medicine (formerly Institute of Medicine) clinical practice guidelines were used as a basis for consensus development with an updated literature search for important studies published between 1992 and 2017 and supplemented, as appropriate, by recommendations from Task Force participants. Results: The Task Force considered patients with stage II-IV melanoma and here provide consensus recommendations for how they would incorporate the many immunotherapy options into clinical pathways for patients with cutaneous melanoma. Conclusion: These clinical guidleines provide physicians and healthcare providers with consensus recommendations for managing melanoma patients electing treatment with tumor immunotherapy.